Pulitzer Prize’s Breaking News Photography Intensifying Students’ Photojournalism - Putu Lirishati Soethama; I Komang Sumaryana (Journal of World Science, 2024)
The recent surge in Pulitzer Prize-winning Breaking News Photography has prompted an exploration into its impact on student photojournalism. This research aims to investigate and analyze this phenomenon. The objective of this study is to assess the effects of recent Pulitzer Prize-winning Breaking News Photography on the intensification of student photojournalism. A qualitative approach, utilizing observational methods, was employed in this research. Sampling was conducted through cluster sampling, involving a total of 60 participants. The analysis of Pulitzer Prize-winning Breaking News Photography indicates a notable enhancement in the ability of students to produce high-quality journalistic photos. Assignments focused on reinforcing the essential principles of journalism have facilitated increased creativity in photo composition and improved accuracy in captioning. Moreover, the evaluation of student works uploaded to social media platforms has provided valuable insights for instructors. Additionally, the need for curriculum adaptation to emphasize skill development is highlighted, aiming to cultivate professional, integrity-driven, and honest journalists. The implications of this study underscore the significance of adapting curriculum structures to bolster skill development in student photojournalists, thereby fostering the emergence of journalism professionals characterized by integrity and honesty.